2010
DOI: 10.1080/03601231003613542
|View full text |Cite
|
Sign up to set email alerts
|

The important characteristics of soil organic matter affecting 2,4-dichlorophenoxyacetic acid sorption along a catenary sequence

Abstract: Variations in the characteristics of soil organic matter (SOM) at the field-scale are largely unknown, particularly in relation to observed variations in herbicide sorption. For the herbicide 2,4-D [2,4-dichlorophenoxyacetic acid], we found that its organic carbon-normalized sorption coefficient, Koc, varied by four-fold, from 76 to 315 L kg(-1), in the Ap-horizon along a slope transect in an undulating agricultural field in Manitoba, Canada. In order to explain the relatively large in-field variation in 2,4-D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 45 publications
(40 reference statements)
0
4
0
Order By: Relevance
“…For nonionic pesticides, hydrophobic bonding (partitioning) is most common, but other possible mechanisms for sorption by HS include charge‐transfer complexes, covalent bonding, hydrogen bonding, and Van der Waals attractions (Senesi and Chen, 1989; Senesi, 1992). Bonding mechanisms commonly observed for ionizable pesticides and HS include charge‐transfer (electron donor–acceptor) complexes, hydrogen bonding, ligand exchange, and Van der Waals attractions (Fusi et al, 1988; Senesi and Chen, 1989; Hermosin and Cornejo, 1993; Piccolo and Celano, 1994; Senesi et al, 1995, 1997; Ferreira et al, 2002; Sheals et al, 2002).…”
Section: Modeling Of Metal Ion Binding In Soilsmentioning
confidence: 99%
“…For nonionic pesticides, hydrophobic bonding (partitioning) is most common, but other possible mechanisms for sorption by HS include charge‐transfer complexes, covalent bonding, hydrogen bonding, and Van der Waals attractions (Senesi and Chen, 1989; Senesi, 1992). Bonding mechanisms commonly observed for ionizable pesticides and HS include charge‐transfer (electron donor–acceptor) complexes, hydrogen bonding, ligand exchange, and Van der Waals attractions (Fusi et al, 1988; Senesi and Chen, 1989; Hermosin and Cornejo, 1993; Piccolo and Celano, 1994; Senesi et al, 1995, 1997; Ferreira et al, 2002; Sheals et al, 2002).…”
Section: Modeling Of Metal Ion Binding In Soilsmentioning
confidence: 99%
“…3) in relation to the results reported by other authors. Farenhorst et al (2010) found in soil from an agricultural field in Manitoba, Canada, proportions of aromatic C (O-aryl C + aryl C) between 24 and 37% of the total area in the of 13 C NMR. Ahmad et al (2006) studied the nature of of 25 soils of Australia and Pakistan and reported proportions of aromatic C between 11 and 28%.…”
Section: Resultsmentioning
confidence: 98%
“…In the last decade, several studies have shown that K OC is a coefficient which depends not only on the adsorbate molecule but also on soil properties (Ahangar et al 2008b;Singh and Kookana 2009;Gebremariam et al 2012;Ehlers Clark et al 2010). Other authors reported that K OC values vary considerably within soillandscape (Coquet and Barriuso 2002;Farenhorst et al 2010) and both intrinsic factors (such as the natural condition of the soil) and extrinsic factors (management practices) can contribute to such variations (Farenhorst 2006). Wauchope et al 2002 analyzed K OC values from many different soils reported by several other authors finding that the coefficient of variation in K OC values was generally around 30-60% and the ratio between the maximum values and minimum values of K OC was generally around 3-10.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation